Reflexões sobre a saúde pública no Maranhão e a sazonalidade dos casos de Covid-19 - Santana, Raquel Pereira; Costa, Thiago Ronyerisson Silva; Mattos Júnior, José Sampaio de (Geoconexões online, 2022)
The Geography of Health is a field of study that is gaining more and more space among geographers. Given the emergence of epidemic outbreaks, and more recently pandemics (COVID-19 in 2019 and still in effect), the relevance of health studies from a geographic perspective is verified. The main objective of this research was to reflect on public health in the state of Maranhão in the face of the health crisis caused by the Covid-19 pandemic, a disease caused by the new severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), identifying the rates of lethality in the state, noting that the capital São Luís and the municipalities of Imperatriz, Açailândia, Balsas, Caxias, Santa Inês and Timon concentrate the largest numbers of confirmed cases.